Medical Rhetoric in the Formation of Communicative Competence of Pediatricians - Elena N. Grinko ("Paediatrician" Publishers LLC, 2017)
In the training of modern doctors, great attention should be paid to the formation of communicative competence, since the success of medical practice is not only related to medical knowledge, but also to communicative skills. Doctor is a linguoactive profession:speech and communication skills are necessary for the doctor in medical, preventive, educational, organizational and management activities. Medical rhetoric as a theory and practice of effective speech behavior in a public monologue and dialogue can contribute tothe preparation of future pediatricians.